Geochronology and Ore‐Forming Fluids of the Baizhangyan W–Mo Deposit in the Chizhou Area, Middle‐Lower Yangtze Valley, SE‐China. Issue 1 (20th December 2012) - Song, Guoxue; Qin, Kezhang; Li, Guangming; Li, Xianhua; Qu, Wenjun
Abstract The Baizhangyan skarn‐porphyry type W–Mo deposit is located in a newly defined Mo–W–Pb–Zn metallogenic belt, which is in the south of Middle‐Lower Yangtze Valley Cu–Fe–Au polymetallic metallogenic belt in SE China. The W–Mo orebodies occur mainly within the contact zone between fine‐grained granite and Sinian limestone strata. There are two types of W–Mo mineralization: major skarn W–Mo mineralization and minor granite‐hosted disseminated Mo mineralization which was traced by drilling at depth. Eight molybdenite samples from Mo‐bearing ores yield Re–Os dates that overlap within analytical error, with a weighted average age of 134.1 ± 2.2 Ma. These dates are in close agreement with SIMS U–Pb concordant zircon age for fine‐grained granite at 133.3 ± 1.3 Ma, indicating that crystallization of the granite and hydrothermal molybdenite formation were coeval and likely cogenetic. The Baizhangyan W–Mo deposit formed in the Early Cretaceous extensional tectonic setting at the Middle‐Lower Yangtze Valley metallogenic belt and the Jaingnan Ancient Continent. Based on mineral compositions and crosscutting relationships of veinlets, hydrothermal alteration and mineralization, the ore mineral paragenesis of the Baizhangyan deposit is divided into four stages: skarn stage (I), oxide stage (II), sulfide stage (III), and carbonate stage (IV). Fluid inclusions in garnet, scheelite, quartz and calcite from W–Mo ores are mainly aqueous‐rich (L + V) type inclusions. Following garnet deposition at stage I, the high‐temperature fluids gave way to progressively cooler, more dilute fluids associated with tungsten–molybdenite–base metal sulfide deposition (stage II and stage III) (162–360°C, 2.7–13.2 wt % NaCl equivalent) and carbonate deposition (stage IV) (137–190°C, 0.9–5 wt % NaCl equiv.). Hydrogen‐oxygen isotope data from minerals of different stages suggest that the ore‐forming fluids consisted of magmatic water, mixed in various proportions with meteoric water. From stage I to stage IV, there is a systematic decrease in the homogenization temperature of the fluid‐inclusion fluids and calculated δ18O values of the fluids. These suggest that increasing involvement of formation water or meteoric water during the fluid ascent resulted in successive deposition of scheelite and molybdenite at Baizhangyan.